Tactical planning in tramp shipping - A literature review - Hannah Pache; Michaela Grafelmann; Anne Kathrina Schwientek; Carlos Jahn (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: This paper discusses the current state of research on tactical planning in tramp shipping problems. The constantly changing demands in operative tramp shipping make tactical or strategical, i.e. longer-term planning, in comparison to operative planning more complex. The purpose of this paper is to describe solutions to tactical planning difficulties in tramp shipping and to point out future research directions. Methodology: For this paper, a systematic literature review of journal articles and book chapters of the last ten years is conducted. The findings of this search are analyzed and reviewed. Thus, different planning problems and their solutions are identified. Findings: Planning problems in tramp shipping are clearly distinct from planning problems in liner shipping as tramp shipping is subject to considerably more uncertainties. Due to the high degree of uncertainties in tramp shipping longer-term planning is challenging. Consequently, the results of research on tactical planning problems in liner shipping cannot be transferred directly to tramp shipping. Originality: This paper provides a comprehensive overview of strategic and tactical planning in tramp shipping as presented in the literature.
urn:nbn:de:gbv:830-882.0115549; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science